The breeding of Malayan tigers (Panthera tigris corbetti) at Zoo Melaka, Department Of Wildlife And National Parks, Malaysia - Zainuddin, Zainal-Zahari (Department of Wildlife and National Parks - Perhilitan, 1992)
The breeding behaviour, age at sexual maturity, estrus, mating, birth and maternal care of captive Malayan tigers at Zoo Melaka are described. Currently, the known captive population of Malayan tigers both locally and internationally are below 30 (International Tiger Studbook, 1992). All the initial captive population originated from Zoo Melaka, Department of Wildlife and National Parks (DWNP), Peninsular Malaysia. Partial and complete habitat degradation have contributed to the degeneration of potentially viable population, loss of primary food source, livestock depredation and consequence poaching by man. The age of sexual maturity, duration of estrus and gestation period averaged 1 year 7 months, 4 days and 103 days respectively. The birth weight of male and female averaged 1575g and 994g respectively. The problems associated with breeding of the Malayan tigers in captivity include breeding space, inadequate founders, compatibility, mate selectivity and cannibalism. The litter size ranged from 2-4 with a male female ratio of 1:3. Three one months old females were hand reared after their dam died of suspected poisoning. The feed offered include powdered milk with taurine (SNOW, Snow brand milk products Co., Ltd, Tokyo, Japan), taurine supplements (Taurine tablets, Pet-Ag, Inc, USA) and canned cat food (WHISKAS, The East Asiatic Company (M) Bhd, Malaysia). The monthly weight gain until the age of 5 months averaged 2.7 kg.